The Aquaponic Cultivation of Catfish in Barrels (Budikdamber) on Internet of Things (IoT) and Fish Pellets from Water Hyacinth as a Food Security Strategy for the Tugu Village Community, Sayung District, Demak - Harianingsih, Harianingsih; Sulistyawan, Vera Noviana; Widiarti, Nuni; Putra, Muhammad Rizky Fahrizal; Sokmawan, Muhammad Rafi Hanairo (Universitas Negeri Semarang, 2024)
Tugu Village in Demak Regency frequently experiences disasters such as coastal erosion and inundation due to tidal activities and the reclamation of Marina Beach in Semarang, which borders Sayung District. These conditions negatively impact the local economy, necessitating a solution to enhance food self-sufficiency. One approach taken is the cultivation of catfish in barrels (budikdamber) using an aquaponic system to grow water spinach, supported by the Internet of Things (IoT). The target audience for this community service activity is the women in Tugu Village affected by flooding. The program was implemented in five stages: observation and coordination, socialization, training, technology application, mentoring, and evaluation. Evaluation was conducted using pre-test and post-test instruments. Before the program, participants' understanding of aquaponic budikdamber was only 32.5%, but after the program, it increased sharply to 95%. Participants' understanding of pellet-making also saw a significant increase, from 10% before the program to 90% afterward. This data indicates that the program implementation successfully improved participants' understanding.